A Pilot Study to Assess the Safety and Efficacy of Umbilical Cord Blood-Derived Mesenchymal Stromal Cells for the Treatment of Synovitis in Horses - Kathryn Seabaugh; Sangeeta Rao; Judith B. Koenig; Lynn Pezzanite; Steven Dow; Thomas G. Koch; Keith A. Russell; Sahar Mehrpouyan; A. Hamed Alizadeh; Laurie R. Goodrich (Animals, 2024)
Synovitis is present before and during osteoarthritis in horses and can result in performance-limiting lameness. Twenty-four horses with lameness localized to the metacarpo-/metatarsophalangeal joint or a single joint of the carpus were enrolled in this study. We evaluated the response of intra-articular injection with 10 million activated (aMSC) or non-activated (naMSC) allogeneic equine umbilical cord blood-derived mesenchymal stromal cells (MSCs). Subjective and objective lameness was assessed on Days 0, 1, 21, and 42. The treatment injection was randomly assigned and performed following the baseline assessment on Day 0. naMSC-treated horses had straight-line lameness scores that were significantly lower on Day 21 (1.0 ± 1.15) and Day 42 (1.13 ± 1.00) than on Day 0 (p = 0.0098 and p = 0.0418, respectively). aMSC-treated horses had straight-line lameness scores that were significantly lower on Day 21 (0.96 ± 1.03) and Day 42 (0.79 ± 1.05) than on Day 0 (p = 0.0011 and p < 0.0001, respectively). There was no significant difference between the treatment groups for any parameter at any timepoint. In conclusion, both aMSC and naMSC allogeneic MSCs resulted in significantly improved subjective lameness scores in horses when compared to baseline lameness scores.